Pengembangan Kota Tiom Sebagai Kawasan Perkotaan Di Kabupaten Lanny Jaya - Risnawati K (Universitas Muslim Indonesia, 2023)
Abstract This research is about the Development of Tiom City as an Urban Area in Lanny Jaya Regency. The main problem is how to develop Tiom City as a Tiom Urban Area by looking at the Basic Physical Aspects and Potential of the Tiom City Area. This problem is seen by looking at the readiness of Tiom City to be developed as an Urban Area, This research uses descriptive qualitative analysis. according to the data obtained, namely classifying and presenting the data in tabular form, descriptions, and drawings, and this analysis is carried out to consider the physical conditions and potential that exist in the research location to support the Development of Tiom City as an Urban Area.